Impact of the English Program Materials in a Public University in Colombia - GONZÁLEZ MARÍN, CLARA INÉS; MARÍN PALACIO, NATHALIA; CARO GUTIÉRREZ, MIGUEL ANTONIO ANTONIO (Universidad Pedagógica y Tecnológica de Colombia, 2018)
This is the report of a research proposal that had as its main purpose the identification of the impact of the materials used for teaching an English language course in the institutional English program of a Colombian university. To this end, we made use of the descriptive research parameters to analyze the materials that were being implemented in the program, and of a pre-experimental research to determine the impact of various and new types of materials in the development of oral skills into two groups of students of the fourth level of English. The information was collected through class observation, field notes, surveys, and semi-structured interviews for both students and teachers. Findings show that the course book and non-authentic materials are prevalent in classes, and that through the new materials designed by the research group, students’ communicative competence was greatly developed